2018
DOI: 10.1016/j.cmet.2018.08.009
|View full text |Cite|
|
Sign up to set email alerts
|

The Translational Machinery of Human CD4+ T Cells Is Poised for Activation and Controls the Switch from Quiescence to Metabolic Remodeling

Abstract: Naive T cells respond to T cell receptor (TCR) activation by leaving quiescence, remodeling metabolism, initiating expansion, and differentiating toward effector T cells. The molecular mechanisms coordinating the naive to effector transition are central to the functioning of the immune system, but remain elusive. Here, we discover that T cells fulfill this transitional process through translational control. Naive cells accumulate untranslated mRNAs encoding for glycolysis and fatty acid synthesis factors and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 57 publications
(77 reference statements)
7
103
0
1
Order By: Relevance
“…Moreover, these changes in real-time respiration are supported by earlier work showing remodeling of glycolysis, the TCA cycle and OXPHOS following T cell activation 29,39,40 .…”
Section: Increased Respiration and Downstream Pathway Signaling In Acsupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, these changes in real-time respiration are supported by earlier work showing remodeling of glycolysis, the TCA cycle and OXPHOS following T cell activation 29,39,40 .…”
Section: Increased Respiration and Downstream Pathway Signaling In Acsupporting
confidence: 73%
“…The association of immune and metabolic states has been extensively studied in T cell biology. Increased utilization of glycolysis, OXPHOS, and fatty acid synthesis following T cell receptor stimulation 1,34,39,[54][55][56] . In this study, we confirmed these findings and further demonstrated the involvement of the PPP, fatty acid oxidation, antioxidant level, and arginine synthesis pathways post activation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that regulation of mRNA translation by mTORC1 is associated with T-cell activation and effector-cell differentiation. 97,98 Studies have shown that the translatome differs among subsets of effector CD8 + or CD4 + T cells. 97,99 Also, T-cell proteome remodeling appears to be largely regulated at the post-transcriptional level in both CD4 + and CD8 + T cells, [100][101][102] implicating protein translation as a major regulator of T-cell activation and differentiation.…”
Section: Translation Of Proteins Via S6k and 4e-bp Pathwaysmentioning
confidence: 99%
“… AbstractActivation of T cells requires a global surge in cellular protein synthesis, which is accompanied by a large increase in translation initiation 14 . A central component of the translation initiation machinery–the multi-subunit eukaryotic initiation factor 3 (eIF3)–is rapidly turned on when quiescent T cells are stimulated 3 .…”
mentioning
confidence: 99%
“…In the immune system, T cell activation involves a burst in translation 14 and correlates with assembly of subunit EIF3J with the main eIF3 complex 3 . However, whether eIF3 serves a general or more specific role in T cell activation is not known.…”
mentioning
confidence: 99%